Dissipation of ¹⁴C-DDT in soil under controlled temperature and field conditions - Andréa, Mara M. de; Ruegg, Elza F.; Tomita, Rúbia Y.; Mesquita, Terezinha B. (Pesquisa Agropecuaria Brasileira, 1991)
The dissipation of 14C-DDT in soil was studied during two years, under ambient temperature and 34°C in the laboratory, and in soil columns in the field. In the laboratory, the jars with soil also contained foam to trap volatile compounds. Half of the jars remained under ambient temperature and the other half was maintained at 34°C. The 14C-DDT mobility was studied in soil columns in the field. All samples were extracted with methanol, and combustion of extracted soil samples was done. Quantification of 14C was performed by liquid scintillation counting. The recoveries of 14C-DDT after two years were about 71% at ambient temperature, 68% at 34°C, and only 1% was collected as volatile products. However, in the field, about 30% of the applied DDT dissipated in the first two weeks. Following, the dissipation was slow and the radiocarbon-activity declined to 44% after 96 weeks. The hal-life of DDT in the field was about 1,000 days, and the compound was almost immobile because very little was detected bellow the 10 cm of the surface.